Resolution of a protracted serogroup B meningococcal outbreak with whole genome sequencing shows inter species genetic transfer. - Mulhall, R; Brehony, C; O'Connor, L; Meyler, K; Jolley, K; Bray, J; Bennett, D; Maiden, M; Cunney, R (American Society of Microbiology, 2016)
A carriage study was undertaken (n=112) to ascertain the prevalence Neisseria spp. following the eighth case of invasive meningococcal disease in young children (5-46 months) and members of a large extended indigenous ethnic minority Traveller family (n=123), typically associated with high occupancy living conditions.Nested Multi Locus Sequence Typing (MLST) was employed for case specimen extracts. Isolates were genome sequenced, then assembled de novo and deposited into the Bacterial Isolate Genome Sequencing database (BIGSdb). This facilitated an expanded MLST approach utilising large numbers of loci for isolate characterisation and discrimination.A rare sequence type 6697 predominated in disease specimens and carried isolates (n=8/14), persisting for at least 44 months, likely driven by the high population density of houses (n=67/112) and trailers (n=45/112). Carriage was more likely in the smaller, more densely populated trailers for N. meningitidis (p<0.05) and N. lactamica (p<0.002) (2-sided Fishers exact test). Meningococcal carriage was highest in 24-39 year olds (45%, n=9/20). Evidence of horizontal gene transfer (HGT) was observed in four individuals co-colonized by Nersseria lactamica and Neisseria meningitidis One HGT event resulted in the acquisition of 26 consecutive N. lactamica alleles.This study demonstrates how housing density can drive meningococcal transmission and carriage, which likely facilitated the persistence of ST6697 and prolonging the outbreak. Whole genome MLST can effectively distinguish between highly similar outbreak strain isolates, including those isolated from person-to-person transmission, and also highlighted how a few HGT events can distort the true phylogenetic relationship between highly similar clonal isolates.